Real-Time Optical Spectrum Fourier Transform With Time–Bandwidth Product Compression - Hao Sun; Xinyi Zhu; Wei Li; Ninghua Zhu; Ming Li (IEEE Photonics Journal, 2018)
We propose and experimentally demonstrate a photonic technique for Fourier transformation of broadband optical spectrum and compression of time-bandwidth product (TBP) simultaneously. Conventionally, an optical spectrum could be Fourier transformed based on the so-called time-spectrum convolution technique with a linearly dispersive delay line. In this paper, a nonlinearly dispersive delay line is implemented by the convolution of an input optical spectrum in the spectral domain with a nonlinearly chirped temporal sinusoidal waveform in the time domain. By specially designing the chirp rate variation of the temporal waveform, an anamorphic Fourier transformation functionality is realized to compress the TBP of output waveform. The key feature of this paper is that it is the first time to our knowledge to carry out the Fourier transformation of an optical spectrum with TBP compression. In addition, since the dispersive delay line could be programmable with high resolution, this technique is adaptable for different optical spectra and realizable for a reconfigurable TBP compression ratio. Experimental results show that the TBP compression ratio is programmable from 1.6 to 3 by engineering the nonlinear dispersive delay line. After reconstructing the Fourier transform of optical spectrum from the output waveforms, the error rate of the recovered waveform is calculated quantitatively. Also, we discussed and proved the possibility to recover the input spectrum only with intensity information. This proposed method is promising to break the big data limitation of the conventional real-time optical spectrum Fourier transformation technique based on the TBP engineering for data compression.